EVALUATION OF SPRING RAPESEED (BRASSICA NAPUS L.) CULTIVARS FOR DIFFERENT PLANTING DATES AND IRRIGATION REGIMES - A. H. Shirani Rad; Z. Bitarafan; F. Rahmani; T. Taherkhani; A. Moradi Aghdam; S. Nasr Esfahani (Journal of Animal and Plant Sciences, 2014)
The effects ofplanting date andirrigation regimes on some physiological and agronomical traitsof spring rapeseed (Brassica napus L.) cultivars were studied through field experiments conducted in Takestan, Iran during 2011-2013. Experiments were laid out in RCBR factorial split plot with two irrigation levels (I1: normal irrigation (non-water stress) and I2: interruption of irrigation from the pod formation stage (water stress)) and three planting dates (D1: February 24, D2: March 6, and D3: March 16) as main plots and three spring cultivars including V1: RGS003, V2: Sarigol, V3: Zarfamas subplots. The results of experiments revealed that water stress and postponing the planting date significantly had a negative influence on rapeseed cultivars.The highest seed yield, biomass yield, seed oil content, leaf relative water content and chlorophyll a and b content obtained in first planting date under normal irrigationby RGS003 althoughin these condition proline content, glucosinolate content, erucic acid content, stomatal resistance, and canopy temperaturehad the lowest means.RGS003 showed superiority in comparison to other cultivars in all planting dates and irrigation regimes as produced higher yields and oil than Sarigol and Zarfamwith lower unfavorable compounds of glucosinolate anderucic acid in all optimum and not optimum conditions.
Keywords: Rapeseed (Brassica napus L.); Irrigation regimes; Planting date; Physiological traits